Correlation of English students’ reading habits and their writing ability - Gusti Rayyan Noor; Dini Noor Arini; Elvina Arapah (International Journal of Educational Studies in Social Sciences (IJESSS), 2022)
While writing is critical in education, it is a difficult skill to master. Reading is one of the many factors that affect writing. Numerous studies have established a link between reading and writing.  With that assumption, this study will examine the relationship between English reading habits and writing ability among students enrolled in the Advanced Writing Course at the English Language Education Study Program of Lambung Mangkurat University. This study adopted a quantitative approach and a correlational design, with students from batch 2018 as the research population. Using a simple random sampling technique, 50 students were randomly selected to serve as samples. A questionnaire was used to ascertain the students' reading habits, whereas a test was used to ascertain their writing abilities. Pearson Product-Moment Coefficient Correlation was then used to determine the correlation between the variables. The result showed that the correlation coefficient was 0.211 and the significance value was 0.141, indicating that H0 is acceptable because of the sig. value was ? 0.05. Therefore, there is a weak and negative correlation between students' reading habits and their writing ability. This occurred because many students with strong reading habits also have weak writing abilities, implying that the correlation between the two variables is weak.  It is suggested that students develop a reading habit by beginning with small steps such as selecting a short, easy-to-read book, setting small goals, making reading enjoyable, making reading friends, and remaining consistent.